Relationship between Family Support and the Incidence of Burnout among Healthcare Workers during the COVID-19 Pandemic - Rahayu Setyowati; Lia Natalia; Rina Nuraeni; Khusnun Zakiyyah (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2022)
Burnout can occur in every healthcare worker who works in hospitals and Comunity Health Centers (CHC), both consciously or unconsciously. Healthcare workers at CHCs are required to make many reports and sometimes there is a possibility to do it at home. Burnout can be experienced by any healthcare worker. There are several factors that may influence the incidence of burnout, namely: ambiguity, multiple role conflicts, work stress, workload and lack of social support. One source of social support comes from family. Family is a place to share stories and issue complaints when individuals experience problems. This study aims to determine the relationship between family support and the incidence of burnout among healthcare workers during the COVID-19 pandemic. This was a uantitative study with a Cross Sectional approach. The populations involved were all healthcare workers at Jati Tujuh Community Health Center Unit as many as 61 people. The samples were selected using total sampling technique. Data were analyzed through univariate analysis using frequency distribution and bivariate analysis using Chi square test. The study results showed that less than half of healthcare workers experienced burnout. Less than half of healthcare workers did not have family support. Furthermore, there was a significant relationship between family support and the incidence of burnout among healthcare workers. Recommendation is proposed for healthcare workers to increase their knowledge about burnout through seminar activities, consultations with experts and families so as to obtain understanding regarding the importance of family support for healthcare workers who are dealing with COVID-19 patients. Furthermore, CHC Unit should provide training for healthcare workers, especially regarding burnout coping mechanisms to overcome burnout among healthcare workers.